First record of Echinogammarus pungens (H. Milne Edwards, 1840) (Crustacea, Amphipoda) from Africa with the checklist of North African freshwater gammarids - REWICZ, T.; RACHALEWSKI, M.; GRABOWSKI, M. (Mediterranean Marine Science, 2014)
Taking into account the vast area of North Africa, the freshwater gammarid fauna of this area remains rather poorly studied. So far, 20 species of the three following genera: Echinogammarus (11 species), Gammarus (8 spp.) and Chaetogammarus (1 sp.) have been reported from the area in literature. Another species, Echinogammarus pungens (H. Milne Edwards, 1840) was found in the river Titria (Oued Titria), north-western Tunisia, in April 2010. Individuals of both sexes including ovigerous females and juveniles were recorded at the site. This is a first report of this species from Tunisia and from North Africa extending the checklist of freshwater gammarid fauna of North Africa to 21 species. Interestingly the species has apparently replaced Echinogammarus tacapensis (Chevreux et Gauthier, 1924), reported from the same section of the Titria River in 1981. Such radical exchange of gammarid fauna and sudden appearance of the species that has never before been recorded from Africa remains mysterious. Two tentative explanations of that phenomenon are taken into account. First, that E. pungens is in fact a circum-Mediterranean species and was simply overlooked in this area before. Second, that the species is a recent migrant to North African inland waters introduced accidentally either by humans or by waterfowl.